Factors Contributing To Medication Errors And Failure To Report Errors Among U29 Nurses In Hospital University Sains Malaysia - Roslaini Che Romli; Chan , Siok Gim (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2015)
This quantitative-oriented research was conducted to identify factors that contributed to errors in dispensing medication among nurses and to understand why nurses did not report their errors in dispensing. In this study a total of 284 U29 nurses participated in focusing on factors contributing to medication errors and failure to report the errors. In this study, analysis of the data collected was made in two sections; dispensing errors and failure to report the errors in giving medication. According to Evans et al. (2006) although nurses may not admit directly to such errors, they expressed their perceptions towards situations described in the questionnaire items as contributing to medication errors among nurses. Almost all in the sample of 284 chose not to report medication errors because they could not identify the cause of dispensing errors; other nurses perceived that the individual involved is not competent in performing the task. Other reasons include fear that the action will be exposed by the management, to avoid publicity from the media, and there is no difference in reporting or not reporting the medication errors. This study was done not only for exploring factors of medication errors; it also aspires to identify problems that arise in hospital services and in order to maintain the quality of health care. The management should consider the impact of medication errors and failure to report medication errors on the nursing profession and quality image of the hospital.